Short Communication: Positional behavior of captive Bornean Orangutan (Pongo pygmaeus) at Bukit Merah Orangutan Island, Perak, Malaysia - SITI NORSYUHADA KAMALUDDIN; SABAPATHY DHARMALINGAM; BADRUL MUNIR MD-ZAIN (Biodiversitas Journal of Biological Diversity, 2019)
Kamaluddin SN, Dharmalingam S, Md-Zain BM. 2019. Short Communication: Positional behavior of captive Bornean Orangutan (Pongo pygmaeus) at Bukit Merah Orangutan Island, Perak, Malaysia. Biodiversitas 20: 425-429. Bukit Merah Orangutan Island (BMOUI) is the only semi-captive orangutan conservation center in the Malay Peninsula. BMOUI promotes orangutan conservation through ex-situ efforts comprising rehabilitation, education, awareness, ecotourism, and research studies. This research aimed to determine the qualitative behavior aspects, especially focusing on the orangutan positional behavior on BMOUI. A focal instantaneous sampling method was carried out for 252 hours from December 2015 to November 2016. The qualitative results showed that the positional behaviors of a Bornean orangutan at BMOUI were divided into nine main categories, as follows: sitting, lying, clinging, forelimb-hindlimb suspension, standing, walking, running, brachiation, and multipositional modes. The most favorable position shown by a captive Bornean orangutan on BMOUI were dominated by sitting and lying postures. The variety of positional modes displayed in a semi-captive condition still maintained Bornean orangutan as the great ape originating from the tropical inhabitants of wooded environments.